A method of CCN centralized control cache decision based on SDN - Hua QU; Yansong LI; Jun LIU; Jihong ZHAO; Ya GUO (Dianxin kexue)
In the software defined networking and content centric networking integration framework,a cache optimi-zation scheme of centralized control was proposed to make full use of global awareness of the control layer for net-work topology and cache resources,and achieve the optimal use of caching resources in the entire network.In this scheme,the particle swarm optimization (PSO) was applied for centralized cache decision-making depending on node edge degree,node importance degree and content popularity.Therefore,the contents were cached in different nodes reasonably.Simulation result shows that the proposed PSO caching scheme achieves larger cache hit rate and lower path stretch than that of LCE scheme,PROB scheme by evaluating the impact of cache size and content popularity on the caching performance.It also shows that PSO scheme significantly reduces the number of cache nodes to replace the cache,making the cache to achieve the overall cache optimization.